Penerapan Prinsip In Criminalibus Probationes Bedent Esse Luce Clariores dalam Pembuktian Tindak Pidana Narkotika di Indonesia - Bayu Saputra; Syamsuddin; Ilham (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the regulation of admissible evidence in the prosecution of narcotics-related crimes in Indonesia and to examine the application of the principle In Criminalibus Probationes Debent Esse Luce Clariores as a normative standard within the criminal evidentiary system. This research employs a normative legal method using both the statutory approach and the conceptual approach. The legal materials utilized consist of primary, secondary, and tertiary legal sources, which were analyzed qualitatively through a comprehensive literature review. The findings indicate that the regulation of evidentiary instruments in narcotics offenses has evolved through the recognition of electronic evidence as a response to the increasing complexity and sophistication of narcotics-related criminal activities. Nevertheless, several issues remain, particularly concerning the legality standards governing the acquisition of evidence and the absence of explicit regulations regarding the legal consequences of unlawfully obtained evidence (unlawful evidence). The study further reveals that the principle In Criminalibus Probationes Debent Esse Luce Clariores plays a significant role in ensuring that criminal sanctions are imposed solely on the basis of evidence that is clear, lawful, credible, and capable of establishing a judge’s conviction through rational assessment. It is concluded that strengthening the application of this principle is essential to achieving a balance between the effectiveness of narcotics crime eradication, legal certainty, and the protection of human rights within the Indonesian criminal justice system.